"Through the Kids . . . We Connected With Our Community": Children as Catalysts of Social Capital. (April 2013) - Wood, Lisa; Giles-Corti, Billie; Zubrick, Stephen R.; Bulsara, Max K.
Both children and adults benefit from living in communities and neighborhoods that are rich in social capital. However, the research literature is relatively silent with respect to the influence that children may play as catalysts for the formation and maintenance of community or family stocks of social capital. This article investigates whether having dependent children living at home play a role in forging adult connections, community involvement, and social capital in a suburban context. The qualitative data were derived from 12 focus groups and the quantitative data from a survey of 339 residents in three Western Australian suburbs. Overall, the quantitative results found that social capital, neighborhood cohesion, and community participation were all significantly higher among respondents with dependent children living at home. The results have implications for urban design and community infrastructure, including the extent to which the built environment caters for children and fosters social connectedness among parents, families, and the broader community.